DIGITAL PLATFORM AS ALTERNATIVE MEDIA FOR WATCHING FILM AT JOGJA-NETPAC ASIAN FILM FESTIVAL (JAFF) 2020 - Perdana, Ganesha (Seni Media Rekam ISI Surakarta, 2021)
Implementing a film festival on a digital platform could be a game-changer for the film industry in the Covid-19 era. It is then crucial to understand the role of digital platforms as a substitute for attending film festivals at JAFF 2020 because, in essence, films require spaces to interact with the audience regardless of the circumstances. This research is a qualitative study employing a case study methodology. The findings suggest that the role of digital platforms in implementing JAFF 2020 can be viewed as a means for a film festival to connect with its audience via new media. Additionally, the use of digital platforms is intended to act as a catalyst and carrier of energy for film crews to rise to the occasion in the face of a pandemic's uncertain conditions.